2019
DOI: 10.3390/ph12030112
|View full text |Cite
|
Sign up to set email alerts
|

Larvicidal and Enzymatic Inhibition Effects of Annona Muricata Seed Extract and Main Constituent Annonacin against Aedes Aegypti and Aedes Albopictus (Diptera: Culicidae)

Abstract: The mosquitoes Aedes aegypti and Aedes albopictus are vectors of arboviruses that cause dengue, zika and chikungunya. Bioactive compounds from plants are environmentally sustainable alternatives to control these vectors and thus the arboviruses transmitted by them. The present study evaluated the larvicidal activity of an acetogenin-rich fraction (ACERF) and its main constituent annonacin obtained from Annona muricata seeds on Ae. aegypti and Ae. albopictus. The larvicidal assays were performed using different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…However, the larvicidal mechanism action of these compounds was not reported. Annonacin isolated from the seed of A. muricata was evaluated for its larvicidal activity on Aedes aegypti and Aedes albopictus larvae [ 202 ]. The greater larvicidal activity was reported against Aedes aegypti with a LC 50 of 2.65 μg/mL compared to Aedes albopictus with LC 50 of 8.34 μg/mL.…”
Section: Pharmacological Activity Of Isolated Compounds From ...mentioning
confidence: 99%
“…However, the larvicidal mechanism action of these compounds was not reported. Annonacin isolated from the seed of A. muricata was evaluated for its larvicidal activity on Aedes aegypti and Aedes albopictus larvae [ 202 ]. The greater larvicidal activity was reported against Aedes aegypti with a LC 50 of 2.65 μg/mL compared to Aedes albopictus with LC 50 of 8.34 μg/mL.…”
Section: Pharmacological Activity Of Isolated Compounds From ...mentioning
confidence: 99%
“…In order to assess whether protein protease inhibitors contribute to the mortality, the extract was digested with Proteinase K. For Annona muricata leaf extract the Proteinase K treatment did not change the protease inhibition significantly and the mortality rate remained the same (Table 5) indicating that that the inhibitor in the extract is not a protein or not degraded by Proteinase K treatment. Rodrigues et al reported the larvicidal effects of A. muricata seed extract against Aedes aegypti and A. albopictus and Annonacin as the major component [35] . But it remains to be seen whether it is the same inhibitor in the leaf showing the larvicidal effect.…”
Section: Toxicity Of Plant Extracts To Fourth Instars Aedes Aegypti Larvae After Proteinase K Treatmentmentioning
confidence: 99%
“…f. & Thomson reported a potential larvicidal activity (LC 5 0 , 6.95 ppm; LC 9 0 , 30.12 ppm) against C. quinquefasciatus mosquito vector. The acetone seed extract (Rodrigues et al 2019). From the above findings, we can conclude that plant-based products can prove to be the best alternatives or effective source for the control of pest species because these products have minimum LC values and biodegradable nature as mentioned above.…”
Section: Bioassay Studies Of Some Herbal Extracts Against the Larvae mentioning
confidence: 99%